Brazil-Africa relations : historical dimensions and contemporary engagements from the 1960s to the present - Seibert, Gerhard, 1954-; Vizentini, Paulo Gilberto Fagundes, 1955- (Woodbridge, Suffolk ; Rochester, NY : James Currey, 2019)
Fills an important gap in the study of Africa's international relations and its engagement with rising economies in the Global South.
Title from publisher's bibliographic system (viewed on 27 Apr 2021).
Keywords: Brazil -- Relations -- Africa; Africa -- Foreign relations -- 1960-; Brazil -- Foreign relations -- 1985-; Brazil -- Foreign relations -- 1964-1985.; Africa -- Relations -- Brazil